Организационно экономические аспекты бережливого производства на машиностроительном предприятии - Smirnov, Artem A; Kremlyova, Nataliia A (St. Petersburg State Polytechnical University Journal. Economics, 2017)
The relevance of the research subject is justified by the fact that the managerial decisions of the engineering enterprise managers have an effect on the flow of creating value for the consumer, the results of which are reflected in the parameters of the operational cycle of the manufacturing-technological system. The organization of sheet metal cutting at engineering enterprises includes many processes associated with lean production, which is aimed at eliminating the losses in the value creation flows. Therefore, the purpose of the study is to develop theoretical provisions and practical recommendations for the organization of sheet metal rational cutting, taking into account business material resources, at an engineering enterprise with a single or small-scale production type, which optimizes the structure of technological costs for production by increasing the sheet metal utilization rate. Based on the analysis of sheet metal cutting, analysis of technological features of sheet metal cutting methods at a small engineering enterprise, a diagram of cutting process has been developed and technological aspects affecting the design of sheet metal cutting charts have been systematized. The authors proposed to consider the cutting sheet metal process as a multilevel cutting system. This approach will allow to organize complex designing of cutting charts and to carry out an assessment of the changes in the market value of sheet metal material resources after cutting. In order to make a reasonable operational decision by the enterprise’s managers on determining sheet metal material resource to a group of business or non-business resources, the logical principles of the algorithm for evaluating and identifying have been developed. This will increase the competitive advantages of products by reducing losses in the organization of cutting sheet metal: the cost of storing and transporting non-business material resources, unit costs for sheet metal. In further research it is necessary to develop a methodology and an algorithm for evaluating and identifying the sheet metal material resources obtained after cutting, the methodology evaluating the market value of nth level material resource, recommendations for organizing management accounting and storing business material resources.